Essential Arabic : Speak Arabic with Confidence! (Arabic Phrasebook) - Mansouri, Fethi (Tuttle Publishing, 2013)
A concise Arabic phrase book and guide to the Arabic Language, Essential Arabic contains basic vocabulary necessary for communicating in Arabic. As Arabic is an official language of 27 countries, many of them of strategic importance to the United States, it is no wonder that Arabic is the fastest-growing language taught at U.S. colleges and universities. Perfect for business people or tourist traveling to the Middle East or for students who want to supplement their learning (and get an A in Arabic!), this book's easy indexing feature allows it to act as an Arabic phrasebook or as a Arabic to Eng.